Reassessing Online Dispute Resolution Frameworks in Indonesia, Malaysia, and the Philippines - Tantimin Tantimin; Michael T. Sacramed; Febri Jaya; David Tan; Ninne Zahara Silviani (QONUN: Jurnal Hukum Islam dan Perundang-undangan, 2026)
This study examines the legal vacuum surrounding cross-platform online dispute resolution (ODR) within Southeast Asian online marketplace ecosystems, particularly where disputes arise from transactions involving integrated third-party services. The objective of this research is to assess the adequacy and consistency of legal frameworks in Indonesia, Malaysia, and the Philippines in accommodating cross-platform ODR. This study employs the doctrinal legal research method and the comparative approach for a deep dive statutory analysis and descriptive examination of primary legal sources across different legal systems. The findings demonstrate that while all three jurisdictions recognize electronic transactions and alternative dispute resolution in principle, none provides comprehensive regulation for cross-platform ODR. Indonesia explicitly acknowledges ODR in its e-commerce regulation but exhibits normative disharmony with its ADR framework. Malaysia’s arbitration and mediation regimes remain structurally unsuitable for low-value, high-volume marketplace disputes. The Philippines introduces a centralized ODR mechanism yet fails to address liability allocation in integrated multi-platform transactions. The legal vacuum identified necessitates an integrated ODR framework capable of ensuring procedural coherence, data coordination, and enforceability. Findings of this study contribute to the effort to understand the implications dispute resolutions in today’s digital economy by highlighting practical implications for scholars and policymakers alike.